DISKUSI DOKTRIN “INTRINSECE MALUM” SEBELUM DAN SESUDAH VERITATIS SPLENDOR - Yustinus . (Litbang STFT Widya Sasana Malang, 2006)
The study examines the debate between the revisionists who wanted to revise or even abandon the doctrine of intrinsece malum ex objecto and the traditionalists who defended it which hinges on three basic issues: 1. Can the morality of the human act be assessed merely from its object independent of circumstances and the agent’s intention? 2. Can universal immutable prohibitive norms be truly absolute and exceptionless in conflict situations? 3. What further theological issues arise from the discussion? After examining their discussions which are situated in before and after Veritatis Splendor, the thesis concludes that the root cause of the debate was the different ways in defining intrinsece malum ex objecto by tradition, particularly that of casuistry and of the ethical theory. While reaffirming the doctrine, Pope John Paul II taught the fundamental points which he meant to reshape the discussion and bring the discourse back to its proper moral theological status.